Factors Influencing Society’s Decision to Donate Waqf in the Bogor Waqf Forest: A Qualitative Study - Faza, Firdan Thoriq (Universitas Muhammadiyah Ponorogo, 2025)
Introduction/Main Objectives: Muslims have varying tendencies when it comes to donating their wealth. Generally, Indonesians donate to mosques, schools, and cemeteries. However, over the past ten years, there has been an increasing trend of donating to nature conservation. This phenomenon raises several questions because it falls outside the